2020
DOI: 10.1007/s11368-020-02785-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration in seven types of temperate forests exhibits similar temperature sensitivity

Abstract: Purpose The aim of the study was to compare the temperature sensitivity of soil respiration rate in two soil horizons of seven types of temperate forests. Materials and methods Soil samples were collected in O and A horizons in seven types of temperate forests, each one represented by five independent stands distributed throughout Poland. Soil respiration rates were measured at standard moisture in five temperatures (4 °C, 10 °C, 16 °C, 22 °C and 28 °C), and the first-order Q10 values were calculated for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Soil respiration (SR) is one of the major pathways of the carbon dioxide e ux from the soil, thus determining SR is the most effective measure to elucidate the carbon emission that could be made accurate in estimation of the global carbon budget (Trumbore 2006). Given their critical role in the global carbon SR measurement and modeling issues have been kept in priority and well studied (Xu and Klimek et al 2021). In this study, the major environmental factor, the ST showed a statistically signi cant exponential effect on SR variations in 2-years (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Soil respiration (SR) is one of the major pathways of the carbon dioxide e ux from the soil, thus determining SR is the most effective measure to elucidate the carbon emission that could be made accurate in estimation of the global carbon budget (Trumbore 2006). Given their critical role in the global carbon SR measurement and modeling issues have been kept in priority and well studied (Xu and Klimek et al 2021). In this study, the major environmental factor, the ST showed a statistically signi cant exponential effect on SR variations in 2-years (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…The two years average seasonal mean SR (282.5 mg CO 2 m −2 h −1 ) of this temperate R. arboreum forest was within the range (90-551 mg CO 2 m −2 h −1 and 98-305 mg CO 2 m −2 h −1 ) of daily mean SR during autumn season in cool-temperate Mongolian Quercus forests in Korea (Kim et al 2020). Due to the complexity of the components and spatially heterogeneous nature of the forest's soil, it is much di cult to understand the environmental variability (Li et al, 2013), and uniquely coupled with other biotic processes, the most common might be the soil properties in generating a broad spectrum of CO 2 emission rates in the temperate forests (Klimek et al 2021). The prior observations by Cui et al (2020) and Kochiieru et al (2021) suggested that it is not surprising that SR rates vary considerably in different seasons, years and in the different forests, eco-zones, and even in the different soils and land use types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, litter decomposition and soil respiration in C cycle have diferent appearance in the temperate forest than that of the tropics [16,17]. Although soil temperature (ST), soil water content (SWC), and the light activity (photosynthetic photon fux density (PPFD)) are considered major environmental criterion in infuencing SR, seasonal fuctuations alter its variability in temporal scale [18] is diferent in temperate ecosystems [14,19,20] than that of the tropical [21,22]. Te temperate forests sequestrate and emit huge volume of atmospheric CO 2 , and that amount could literally contribute a signifcant role in the global C cycle [2].…”
Section: Introductionmentioning
confidence: 99%
“…Te recently published data however indicated that temperate forests are an important sink of atmospheric C [23]. Tus, the research interest in a temperate forest is growing under the context of climatic warming [20,24]. About 23% of Nepal's land area has been designated under various categories of protected area which includes national parks, reserves, conservation areas, and buferzones [25].…”
Section: Introductionmentioning
confidence: 99%